High-quality draft genome sequences of Pseudomonas monteilii DSM 14164T, Pseudomonas mosselii DSM 17497T, Pseudomonas plecoglossicida DSM 15088T, Pseudomonas taiwanensis DSM 21245T and Pseudomonas vranovensis DSM 16006T: taxonomic considerations. Issue 10 (29th December 2019) - Peña, Arantxa; Busquets, Antonio; Gomila, Margarita; Mulet, Magdalena; Gomila, Rosa M.; Garcia-Valdes, Elena; Reddy, T. B. K.; Huntemann, Marcel; Varghese, Neha; Ivanova, Natalia; Chen, I-Min; Göker, Markus; et al.
Abstract : Pseudomonas is the bacterial genus of Gram-negative bacteria with the highest number of recognized species. It is divided phylogenetically into three lineages and at least 11 groups of species. The Pseudomonas putida group of species is one of the most versatile and best studied. It comprises 15 species with validly published names. As a part of the Genomic Encyclopedia of Bacteria and Archaea (GEBA) project, we present the genome sequences of the type strains of five species included in this group: Pseudomonas monteilii (DSM 14164 T ), Pseudomonas mosselii (DSM 17497 T ), Pseudomonas plecoglossicida (DSM 15088 T ), Pseudomonas taiwanensis (DSM 21245 T ) and Pseudomonas vranovensis (DSM 16006 T ). These strains represent species of environmental and also of clinical interest due to their pathogenic properties against humans and animals. Some strains of these species promote plant growth or act as plant pathogens. Their genome sizes are among the largest in the group, ranging from 5.3 to 6.3 Mbp. In addition, the genome sequences of the type strains in the Pseudomonas taxonomy were analysed via genome-wide taxonomic comparisons of ANIb, gANI and GGDC values among 130 Pseudomonas strains classified within the group. The results demonstrate that at least 36 genomic species can be delineated within the P. putida phylogenetic group of species.